DEBT SETTLEMENT EFFORT IN THE PERSPECTIVE OF DONATION OF DEBT PAYMENT OBLIGATIONS - Izzy Al Kautsar (Fakultas Hukum Universitas Djuanda Bogor, 2022)
Alternative that can be taken in overcoming the fulfillment of debt payments when running a business by a company by holding debt service obligations postponed. in essence, an alternative will lead the parties to resolve the problem of debt repayment, this alternative is effective and impartial, but in practice the debtor deliberately submits the postponement of the payment obligation in order to minimize his debt bills and creditors who deliberately did not accept the peace agreement, so the debtor was immediately declared bankrupt.